Genetic Diversity and Conservation Status of Helianthus verticillatus, an Endangered Sunflower of the Southern United States - Edwards, Tyler P.; Trigiano, Robert N.; Ownley, Bonnie H.; Windham, Alan S.; Wyman, Christopher R.; Wadl, Phillip A.; Hadziabdic, Denita (Frontiers in Genetics, 2020)
Evaluating species diversity and patterns of population genetic variation is an essential aspect of conservation biology to determine appropriate management strategies and preserve the biodiversity of native plants. Habitat fragmentation and potential habitat loss are often an outcome of a reduction in naturally occurring wildfires and controlled prescribed burning, as seen in Helianthus verticillatus (whorled sunflower). This endangered, wild relative of the common sunflower, H. annuus, is endemic to four locations in Alabama, Georgia, and Tennessee, U.S.A. Despite its endangered status, there is no recovery plan for H. verticillatus, and knowledge related to its basic plant biology and importance in ecosystem services is mostly unknown. In this study, we utilized 14 microsatellite loci to investigate fine-scale population structure and genetic diversity of H. verticillatus individuals found on two sampling sites within the Georgia population. Our results indicated moderate genetic diversity and the presence of two distinct genetic clusters. Analyses of molecular variance indicated that the majority of variance was individually based, thus confirming high genetic differentiation and limited gene flow between H. verticillatus collection sites. The evidence of a population bottleneck in these sites suggests a recent reduction in population size that could be explained by habitat loss and population fragmentation. Also, high levels of linkage disequilibrium were detected, putatively suggesting clonal reproduction among these individuals. Our study provides a better understanding of fine-scale genetic diversity and spatial distribution of H. verticillatus populations in Georgia. Our results can underpin an original recovery plan for H. verticillatus that could be utilized for the conservation of this endangered species and to promote its persistence in the wild.